Interpreters and interpreting in conflict zones and scenarios: A historical perspective - Ruiz Rosendo, Lucía; Persaud, Clementina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This article presents an overview of interpreting in conflict zones and scenarios in different periods of history as represented in the papers included in the special issue. Conflict between parties with different cultural and linguistic backgrounds is pervasive in human history and has always involved interpreters in the sense of intercultural and linguistic mediators. Although interpreting became highly professionalized from the second half of the twentieth century, language brokering in conflict zones is still an unregulated occupation mainly pursued by untrained interpreters. Furthermore, there is a lack of recognition of the specific role that interpreters in conflict situations play. In spite of an increasing awareness of the role of interpreters in conflict zones and an expanding scholarly literature on the subject, we believe that more studies adopting a historical standpoint are needed. The aim of this special volume is to shed light on the characteristics, ideology, status, neutrality, occupation, role in the different stages of the conflict, training issues, and working practices and procedures of interpreters in conflict zones.